2015
DOI: 10.6004/jnccn.2015.0005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Fusion Gene,IRF2BP2-RARA, in Acute Promyelocytic Leukemia

Abstract: Acute promyelocytic leukemia (APL) is characterized by fusion of RARA with PML, or rarely other gene partners. We report a patient with APL with a novel fusion between RARA and the interferon regulatory factor 2 binding protein 2 (IRF2BP2) genes. A 19-year-old woman presented with ecchymoses and epistaxis. Bone marrow examination showed morphologic and immunophenotypic features consistent with APL. PML oncogenic domain antibody was positive. Conventional cytogenetics, FISH, RT-PCR and oligonucleotide microarra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 22 publications
1
48
0
Order By: Relevance
“…Koeppel et al have shown that IRF2BP2 is a transcriptional target of p53, promotes the proliferation of U2OS cells and accelerates cellular resistance to apoptosis induced by doxorubicin and actinomycin D treatment by inhibiting the p53‐mediated transactivation of the P21 and BAX genes. Whole transcriptome sequencing identified a novel IRF2BP2‐caudal type homeobox 1 fusion protein in mesenchymal chondrosarcoma and an IRF2BP2‐retinoic acid receptor alpha fusion protein in acute promyelocytic leukaemia . These studies suggest that IRF2BP2 may play a role in tumorigenesis and cancer progression.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Koeppel et al have shown that IRF2BP2 is a transcriptional target of p53, promotes the proliferation of U2OS cells and accelerates cellular resistance to apoptosis induced by doxorubicin and actinomycin D treatment by inhibiting the p53‐mediated transactivation of the P21 and BAX genes. Whole transcriptome sequencing identified a novel IRF2BP2‐caudal type homeobox 1 fusion protein in mesenchymal chondrosarcoma and an IRF2BP2‐retinoic acid receptor alpha fusion protein in acute promyelocytic leukaemia . These studies suggest that IRF2BP2 may play a role in tumorigenesis and cancer progression.…”
Section: Introductionmentioning
confidence: 83%
“…IRF2BP2 has been reported to be involved in the malignancy of breast cancer, leukaemia and chondrosarcoma . The TCGA database revealed that the IRF2BP2 gene was amplified in most tumours, including GC.…”
Section: Discussionmentioning
confidence: 99%
“…Corresponding reciprocal fusion genes, RARα-PML , RARα-ZBTB16 , RARα-NPM , and RARα-FIP1L1 , are expressed and exist with the rest of the reciprocal fusion genes that have yet to be identified [7,8,9,30,65,72,76,85,98]. The reciprocal product potentially contains the N-terminal transactivation domain of the RARα protein that is linked to the C-terminal domains of the fusion partner.…”
Section: Introductionmentioning
confidence: 99%
“…To date, 11 variant fusion genes in APL, all involving the RARα gene, have been reported in a small percentage of APL cases. The partner genes include zinc finger and BTB domain-containing 16 ( ZBTB16 ; 11q23), nucleophosmin ( NPM ; 5q35), nuclear mitotic apparatus ( NuMA ; 11q13), signal transducer and activator of transcription (STAT) 5β ( STAT5b ; 17q21), protein kinase A (PKA) regulatory subunit type ( PRKAR1A ; 17q24), FIP1-like 1 ( FIP1L1 ; 4q12), BCL6 corepressor ( BCoR ; Xp11), oligonucleotide/oligosaccharide-binding fold-containing 2A ( OBFC2A ; 2q32) [6], transducin β-like 1 X-linked receptor 1 ( TBLR1 ; 3q26) [7], general transcription factor II-I ( GTF2I ; 7q11.23) [8], and interferon regulatory factor 2 binding protein 2 ( IRF2BP2 ; 1q42.3) [9]. The X-RARα (X:partner product) fusion pattern highlights the central role of RARα in the pathogenesis of APL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation